2001
DOI: 10.1096/fj.00-0273com
|View full text |Cite
|
Sign up to set email alerts
|

Activation of paracrine TGF‐β1 signaling upon stimulation and degranulation of rat serosal mast cells: a novel function for chymase

Abstract: As a source of transforming growth factor beta1 (TGF-beta1), mast cells have been implicated as potential effector cells in many pathological processes. However, the mechanisms by which mast cells express, secrete, and activate TGF-beta1 have remained vague. We show here by means of RT-PCR, immunoblotting, and immunocytochemistry that isolated rat peritoneal mast cells synthesize and store large latent TGF-beta1 in their chymase 1-containing secretory granules. Mast cell stimulation and degranulation results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
133
1
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(140 citation statements)
references
References 49 publications
3
133
1
3
Order By: Relevance
“…Potentially, the action of mast cell‐released proteases could either lead to proteolytic activation of cytokines, or to cytokine degradation and destroyed biological activity. In accordance with the former possibility, there are reports suggesting that mast cell serine proteases can proteolytically activate certain cytokines 31, 32, 33 and chemokines 34, 35. Conversely, protease‐dependent degradation of cytokines by human mast cells has previously been demonstrated 6, 12.…”
Section: Discussionsupporting
confidence: 56%
“…Potentially, the action of mast cell‐released proteases could either lead to proteolytic activation of cytokines, or to cytokine degradation and destroyed biological activity. In accordance with the former possibility, there are reports suggesting that mast cell serine proteases can proteolytically activate certain cytokines 31, 32, 33 and chemokines 34, 35. Conversely, protease‐dependent degradation of cytokines by human mast cells has previously been demonstrated 6, 12.…”
Section: Discussionsupporting
confidence: 56%
“…In some systems CD44 has been shown to act as a docking site for proteolytically active MMP-9 (57); immobilized active MMP-9 then cleaves latent TGF-␤ to its active form (58). Interestingly, while mast cell-derived chymase has been shown to release latent TGF-␤ from epithelial cell cultures (59), it has a variable ability to activate latent TGF-␤ directly (51,59,60). One could speculate that local release of chymase by mast cells, and potentially by ASM cells (61), activates MMP-9 and induces the release of latent TGF-␤, which, in turn, is activated by either MMP-9 or chymase.…”
Section: Discussionmentioning
confidence: 99%
“…Lindstedt et al (18) recently reported that TGF-␤1 was stored as latent form in secretary granules of mast cells, that was rapidly released and converted into active form by co-released chymase1 upon mast cell activation. It is therefore possible that LPS induced endogenous TGF-␤1, which could then suppress mast cell responses to LPS in an autocrine manner.…”
Section: Neutralizing Tgf-␤ Activity Enhances Lps-induced Cytokine Prmentioning
confidence: 99%